EDUKASI PREVENTIF PELECEHAN DAN KEKERASAN SEKSUAL TERHADAP ANAK USIA 7-8 TAHUN MELALUI PENGGUNAAN MEDIA APLIKASI SAM.KIDS - Selvi Afmailia; Gina Silvia; Ray Fadly Hadi; Farah Rakhimy Az Zahra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Kementerian Pemberdayaan Perempuan dan Perlindungan Anak Republik Indonesia reported a 15% increase from 4,000 cases of sexual violence against children in 2022. This study aims to develop and determine tool in educating children aged 7–8 years about sexual abuse and violence. The research method used was Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The results indicate that the SAM.Kids application is valid, practical, and effective in improving children's knowledge and preventive behaviors regarding sexual harassment and violence.